On the solutions of a class of nonlinear integral equations in cone $b$-metric spaces over Banach algebras - L.T. Quan; T. Van An (Karpatsʹkì Matematičnì Publìkacìï, 2019)
In this paper, we study the existence of the solutions of a class of functional integral equations by using some fixed point results in cone $b$-metric spaces over Banach algebras. In order to obtain these results we introduced and proved some properties of generalized weak $φ$-contractions, in which the $φ$ are nonlinear weak comparison functions. The obtained results are generalizations of results of Van Dung N., Le Hang V. T., Huang H., Radenovic S. and Deng G. Also, some suitable examples are given to illustrate obtained results.